Renal denervation modulates angiotensin receptor expression in the renal cortex of rabbits with chronic heart failure - Clayton, Sarah C; Haack, Karla K V; Zucker, Irving H (American journal of physiology. Renal physiology, 2011)
Excessive sympathetic drive is a hallmark of chronic heart failure (HF). Disease progression can be correlated with plasma norepinephrine concentration. Renal function is also correlated with disease progression and prognosis. Because both the renal nerves and renin-angiotensin II system are activated in chronic HF we hypothesized that excessive renal sympathetic nerve activity decreases renal blood flow in HF and is associated with changes in angiotensin II type 1 receptor (AT1R) and angiotensin II type 2 receptor (AT2R) expression. The present study was carried out in conscious, chronically instrumented rabbits with pacing-induced HF. We found that rabbits with HF showed a decrease in mean renal blood flow (19.8±1.6 in HF vs. 32.0±2.5 ml/min from prepace levels; P<0.05) and an increase in renal vascular resistance (3.26±0.29 in HF vs. 2.21±0.13 mmHg·ml(-1)·min in prepace normal rabbits; P<0.05) while the blood flow and resistance was not changed in HF rabbits with the surgical renal denervation. Renal AT1R expression was increased by ∼67% and AT2R expression was decreased by ∼87% in rabbits with HF; however, kidneys from denervated rabbits with HF showed a near normalization in the expression of these receptors. These results suggest renal sympathetic nerve activity elicits a detrimental effect on renal blood flow and may be associated with alterations in the expression of angiotensin II receptors.